Lumbar ossification of the ligamentum flavum reflects a strong ossification tendency of the entire spinal ligament - Kazuha Nakabachi; Tsutomu Endo; Masahiko Takahata; Ryo Fujita; Yoshinao Koike; Ryota Suzuki; Yuichi Hasegawa; Toshifumi Murakami; Katsuhisa Yamada; Hideki Sudo; Mohamad Alaa Terkawi; Ken Kadoya; et al. (Scientific Reports, 2023)
Abstract Patients with ossification of the ligamentum flavum (OLF) in the lumbar spine may be at high risk of developing concomitant ossification of the entire spinal ligament, but the etiology remains unclear. We investigated the propensity for spinal ligament ossification in asymptomatic subjects with lumbar OLF using the data of 595 Japanese individuals receiving medical check-ups, including computed tomography (CT) scanning. The severity of OLF (total number of intervertebral segments with OLF) of the entire spine on CT was quantified using an OLF index. Subjects with OLF were grouped according to this index: localized OLF (n = 138), intermediate OLF (n = 70), and extensive OLF (n = 31). The proportion of subjects with lumbar OLF increased with increasing OLF index (localized 13.7%, intermediate 41.4%, and extensive 70.9%). Multiple regression analysis found that lumbar OLF index was associated with thoracic OLF index, and co-existence of ossification of the posterior longitudinal ligament (OPLL) of the thoracic and lumbar spine. This study showed that subjects with more multilevel lumbar OLF were more likely to develop multilevel thoracic OLF and to have coexisting OPLL. Patients with lumbar OLF may be a distinctive subgroup with a strong tendency to ossification of the entire spinal ligament.